PENGELOLAAN INSTAGRAM @DISKOMINFO.BUKITTINGGI SEBAGAI MEDIA INFORMASI KOTA BUKITTINGGI - Nofita Ayu; Penmardianto (ADISAM PUBLISHER, 2023)
Communication and information technology is increasingly advanced and developing rapidly, this phenomenon makes it easier for people to use electronic devices, namely the internet. Software such as poly and social media to communicate more diversely called new wave technology, is a technology that connects individuals and groups. Technological developments in the increasingly rapid era of globalization, present social media. Instagram is one of the social media that is currently widely used by people of all ages, regardless of age. Instagram is currently one of the media for obtaining information, so that many users spread information through Instagram social media, such as the Instagram account @diskominfo.bukittinggi, which uses Instagram as a medium for conveying messages. The account @diskominfo.bukittinggi is included in the top 3 of the number of followers in West Sumatra, and this account only uploads most of its posts only about the mayor of Bukittinggi and the Bukittinggi Kominfo agency. This study uses a type of research that is descriptive qualitative in nature, which describes how Instagram @diskominfo.bukittinggi is managed as an information medium for the city of Bukittinggi. Collecting data using the method of observation, interviews and documentation. Through interview and observation methods, it is known that the main subject to be researched is the @diskominfo.bukittinggi account admin, and the object of this research is the management of @diskominfo.bukittinggi in collecting information so that it becomes information on Instagram posts. The results of the research that has been carried out by researchers can be concluded, namely: (1) the @diskominfo.bukittinggi account in obtaining information, namely by SKPD or direct directions from the Mayor's schedule. (2) the @diskominfo.bukittinggi account processes information by compiling messages, namely selecting photos and videos and creating captions that clarify Instagram users in obtaining information. (3) submission of account information @diskominfo.bukittinggi using existing features on Instagram such as feeds, instastories